Market Opportunities for Green Upgrading and Innovation : Sustainability Demand Analysis for the Beef, Soy, Dairy and Tourism Industries - Criscuolo, Alberto; Cuomo, Francesco (World Bank, Washington, DC, 2018)
Uruguay's export-led growth model depends heavily on its rich base of natural assets. Although innovative environmental initiatives have been implemented and boosted trade competitiveness, the identification of green market opportunities with higher added value, may benefit economically to Uruguay as well as promote sustainable use of natural resources.In this sense, the report presents an economic analysis of the demand for green segments in international markets focusing on the main export sectors (beef, dairy products, soybeans and tourism). These sectors were selected for their great contribution to exports and their intensive use of Uruguay's natural assets. Greener – or more environmentally friendly - products can increase the diversification of exports to niches of higher added value, promoting investments in capacity building and the adoption of new technologies and practices.The report analyzes and delves into the differences between several "green" and "sustainable" beef labels. In terms of green soybeans, the report specifically focuses on non-genetically modified (non-GM) soybeans for their long-term environmental benefits. In terms of dairy products, this report focuses on organic dairy products, due to significant economic premiums and environmental and animal health benefits associated with organic labels. The analysis of these markets, in terms of geography, centers on the main export destinations of Uruguay, such as the European Union, the United States and Asia, including China. The analysis carried out on sustainable tourism focuses on adventure tourism and ecotourism.The report finds that there are important growth prospects and attractive mark-ups in the segments of sustainable beef, non-genetically modified soybeans and organic dairy products, and a potential to strengthen Uruguay's international supply of sustainable tourism. In addition to the economic benefits, these segments can bring important environmental co-benefits associated with the sustainable production and processing practices of "green" value chains. For example, reduction in greenhouse gases emissions, reduction in the use of pesticides and herbicides, soil preservation, reduction on nutrient pollution, among others.In general, this report sheds light on niches of strong demand that could offer new opportunities to Uruguay, and provides recommendations for future work. Among the four sectors analyzed, a low hanging fruit is associated with sustainable beef. In addition, Uruguay could potentially explore the niche of organic milk powder. To make the most of the growth opportunities in the tourism market, currently focused on "beach and sun", the report includes recommendations to diversify and improve the existing supply.This report is part of a series of five complementary analytical products generated under the World Bank's Green Growth Technical Assistance in Uruguay.